The Difference of Efficacy Between Granule Form of Pandan Wangi Leaf (Pandanus amaryllifolius Roxb.) Extract and Abate Against Aedes aegypti L. - Khotimah, Dewi Nur; Handayani, Sutartinah Sri; Haryati, Sri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Abatisasi is considered quite effective against Aedes aegypti L. as a dengue hemorrhaegic fever vector. Improperly use of abate dose can interfere human health and prolonged use can cause larvae resistance so that need an alternative larvicide. Granule of pandan wangi leaf extract (Pandanus amaryllifolius Roxb.) has a potention to be an alternative larvicide. This study aims to determine the effectiveness differences between pandan wangi leaf extract granule with abate against Aedes aegypti L. Methods: This study uses a quasi-experimental methodÂ with the approach posttest only control group design. This study was conducted in September and October 2014 in B2P2VRP Salatiga using the inclusion and exclusion criteria have been determined. The sampling technique used is incidental sampling. The independent variable is abate and pandan wangi leaf extract granule, while the dependent variable is the number of Aedes aegypti L. larvae instar III that be dead. Researcher compare into two different groups, namely pandan wangi leaf extract granule with various concentrations and abate. The data analysis used is One Way ANOVA continuing with LSD test and Probit Analysis. Results: The effectiveness of pandan wangi leaf extract granule is more lower than abate. The result of One Way ANOVA test shows a significance value p <0:01 (p <0.05), which means that there is a significant difference in mortality between the treatment group of larvae and the differences is statistically significant. The result of LSD test shows that abate 1% is significantly different with pandan wangi leaf extract granule 1.5%, 3.5% and 8%, while abate 1% is not significantly different with pandan wangi leaf extract granule 12.5% and 17%. The result of Probit Analysis shows LC50 is 7.007% and LC99 is 94,745%. Conclusions: There is an effectiveness difference between pandan wangi leaf extract granule with abate to against Aedes ageypti L. larvae. Keywords: Aedes aegypti L., pandan wangi leaf extract granule, abate.Â